Business Plan - Kampong House Penang - CHUA, SONG JUN (2016)
Kampong House Penang (Kampong) is a proposed business plan for the redevelopment of an existing family-owned seaside property and 10,000sqft land at Teluk Bahang beach, Malaysia into Penang’s first seaside location luxury 4-star village-themed B&B. Kampong’s core operation is a premium accommodation business offering 10 romantic-themed couple-oriented king suites within a traditional Malay architecture that houses Malaysia’s first B&B mini lazy river. Meanwhile, Kampong’s secondary business operations include B&B room services, romantic-themed couple DIY activities, culture-themed travel packages and on-site event hosting services available to be bundled as all-in-one, personalised, customisable travel and accommodation packages. Essentially, Kampong’s business plan is estimated to cost start-up capital of MYR2,114,377.45 approximately £400k investment to access targeted a Penang couple-oriented tourism sector (2.2m targeted market size, 55% domestic and 45% international tourists segmented into three couple groups: young (18-24), adult (25-35), senior (55-65)) corresponding to a targeted market value of MYR1.1billion ≈ £202m. As a quick snapshot, our investment strategy is breakdown into 76% (MYR1.6m) construction and renovation costs, 8% (MYR160k) construction contingency, 3% (MYR64k) normal scenario working capital requirement, 13% (MYR273k) worst case scenario working capital contingency and 1% (MYR15k) intangible start-up expenses. Financially, our main objective is a conservative market penetration goal of achieving Penang market-level AOR performance within 3 operating years i.e. annual AOR levels of 33% (2018), 51% (2019) and 68% (2020). This realistically conservative goal corresponds to a forecasted breakeven-point by Y2Month5 (NPM at -18%(Y1), 4%(Y2) and 14%(Y3-Y5) correlating to 50%, 75% and 100% AOR performances), and yield a realistically competitive payback period of 8.91 years. Kampong’s long-term (≥5 years) goal is to establish itself as a top-ranked, reputable luxury B&B franchise brand. However, flexible exit strategies (expansion, property sale, business takeover, franchising) are prepared in Y0 (after completion of redevelopment works) and Y3 (after 3 years of business operations) to safeguard investor interests. Operationally, we differentiate ourselves with Blue Ocean Strategy unique selling propositions (USPs) that offer customers four main value propositions in price competitiveness, authentic experience, personalisation convenience and widespread online accessibility convenience. Our market entry strategies combine a competitor-oriented, seasonal pricing model with heavy online promotion via preferential (20% commission) OTA marketing and customer-oriented social media engagement. We also rely on our management team’s nationwide guanxi people network for effective word-of-mouth advertising, tour agencies partnerships and tourism events participations. Moreover, Kampong employs an operating model that outsources non-core business operations (i.e. F&B, cleaning, laundry, security, landscaping) to maintain our strong core focus with added flexibility of professional outsourced services for high cost-value performances. Finally, our five main reasons to invest in Kampong’s business plan are firstly, a unique set of USPs being unmatched by all Penang direct and indirect competitors which equip us with strong competitive and first mover advantages. Secondly, our primary data has indicated positive (89%) initial customer interest that suggest good business potential. Thirdly, secondary data has deducted Penang tourism as a steadily growing (10-year annual average 3.5% size growth) market outperforming the national average in AOR hotel performance and stronger resistance towards external shocks. Fourthly, we have a competent team with tourism passion, SME experience, local market knowledge, extensive people network. Fifthly, our financial preparation with the investment amount is fundamentally solid while our conservative projection will yield a competitive financial performance of 17 months’ breakeven and 8.91 years’ payback (compared to common market performance of 12-24 months for payback and approximately 10 years for payback period).